Basic Characterization of Natural Transformation in a Highly Transformable Haemophilus parasuis Strain SC1401 - Dai, Ke; He, Lvqin; Chang, Yung-Fu; Cao, Sanjie; Zhao, Qin; Huang, Xiaobo; Wu, Rui; Huang, Yong; Yan, Qigui; Han, Xinfeng; Ma, Xiaoping; Wen, Xintian; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Haemophilus parasuis causes Glässer’s disease and pneumonia, incurring serious economic losses in the porcine industry. In this study, natural competence was investigated in H. parasuis. We found competence genes in H. parasuis homologous to ones in H. influenzae and a high consensus battery of Sxy-dependent cyclic AMP (cAMP) receptor protein (CRP-S) regulons using bioinformatics. High rates of natural competence were found from the onset of stationary-phase growth condition to mid-stationary phase (OD600 from 0.29 to 1.735); this rapidly dropped off as cells reached mid-stationary phase (OD600 from 1.735 to 1.625). As a whole, bacteria cultured in liquid media were observed to have lower competence levels than those grown on solid media plates. We also revealed that natural transformation in this species is stable after 200 passages and is largely dependent on DNA concentration. Transformation competition experiments showed that heterogeneous DNA cannot outcompete intraspecific natural transformation, suggesting an endogenous uptake sequence or other molecular markers may be important in differentiating heterogeneous DNA. We performed qRT-PCR targeting multiple putative competence genes in an effort to compare bacteria pre-cultured in TSB++ vs. TSA++ and SC1401 vs. SH0165 to determine expression profiles of the homologues of competence-genes in H. influenzae. Taken together, this study is the first to investigate natural transformation in H. parasuis based on a highly naturally transformable strain SC1401.